(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
Wikipedia is a free, polyglot and collaborative encyclopedia. The article reviews the Editathon 40 years of democracy in Córdoba, a collective editing meeting aimed at improving content related to the period of democratic restoration in Argentina, with a focus on provincial politics, guild issues, and gender. The process took place during the first semester of 2023, a period in which the necessary content and sources were surveyed, interventions were planned and implemented. The experience demonstrates an articulation between teaching, research and extension, aiming to contribute to the debate on emerging approaches through technologies and digital platforms. The balance highlights the skills generated, the adaptation to a broad writing registry and the creation of high-impact content between the university and the Wikimedia community, on human rights topics.